Kajian Aspek Keselamatan Taksi Online di Jakarta - Meygie Dwi Chatrin Marpaung; Suripno Suripno; Sarinah Sihombing (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of the study is to analyse the safety aspect of online taxi as operated private vehicle. Due to high demand of transportation nowadays, many transportation systems based application that attract many users are developed. One of them is online taxi. However, the safety aspect is still questioned. This study was using descriptive evaluative. The study of document and data from the interview were analysed to get the legal formal. The users of the transportation systems based app, the operators, and the regulators as the related parties were interviewed. The analyses show that there are desirable and undesirable results. After the results were reducted and concluded, these parties agree to do the technical test on online taxi to assure the transportation system based app safety used by passengers.